Integration of distributed generators into power system for loss minimization and voltage stability: article / Mohd Khairul Fikri Mohd Salleh - Mohd Salleh, Mohd Khairul Fikri (2009)
This paper describes the integration of distributed generators (DG) into the power system to analyze the losses and voltage stability. The location of DG is based on the weakest bus determined heuristically with the objectives to minimize losses and to improve the voltage stability. The size of DG can be integrated at the weakest bus. Load flow analysis is used to simulate the power loss and voltage profile of the system. The proposed method was applied to a 6-bus and 14-bus IEEE system to show its capability and feasibility. All simulations were done using the MATLAB version 7.6 programming.